2018
DOI: 10.4103/aer.aer_142_17
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary arrest and pneumoencephaly developing after epidural oxygen-ozone mixture therapy

Abstract: Pain treatment can comprise a combination of pharmacological, interventional, surgical, physical, psycological methods. Interventional procedures, particularly minimally invasive percutaneous therapies, have been widely used in recent years. Corticosteroid, hyperbaric saline or oxygen-ozone therapy is a safe procedure for patients in whom pain cannot be relieved by epidural adhesiolysis or other treatments. Complication related to oxygen-ozone therapy have been reported rarely in lumbar sciatalgia. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Our study used a 13‐mm injector tip. A case of cardiopulmonary arrest has been reported after O 3 /O 2 injection in the epidural cavity . No major complication has been reported with lumbar paravertebral ozone injection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study used a 13‐mm injector tip. A case of cardiopulmonary arrest has been reported after O 3 /O 2 injection in the epidural cavity . No major complication has been reported with lumbar paravertebral ozone injection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have also reported on available scientific evidence concerning the beneficial properties of ozone therapy of pain, resulting in ozone therapy being widely used in pain management 19,20. However some complications of oxygen-ozone therapy still exist, such as headache pain, pneumocephalus, and cardiopulmonary arrest 21,22…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 However some complications of oxygen-ozone therapy still exist, such as headache pain, pneumocephalus, and cardiopulmonary arrest. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Ozone can be administered as a gas mixture of oxygen-ozone (medical-grade ozone), with a concentration between 10 and 40 µg/mL [23][24][25][26] . However, a study on the therapy with low (10 µg/mL), medium (40 µg/mL), and high (60 µg/mL) concentrations in patients with disc herniation showed a higher rate of decline in the group who received a volume of 40 µg/ml 25.…”
Section: Types Of Administration Doses and Concentrationsmentioning
confidence: 99%